Utilisation and Perception of Complementary and Alternative Therapies (CATs) among Obese and Overweight Individuals in a Malaysian Public University - Lua, Pei Lin; Roslim, Nurul Afiedia; Ahmad, Aryati; Mansor, Mardiana; Aung, Myat Moe Thwe; Hamzah, Farrahdilla (IIUM Medical Journal Malaysia, 2021)
Introduction: Obesity and overweight are among the most serious public health issues that can threaten the well-being of individuals. Its increasing prevalence in Malaysia has inevitably caused many to additionally seek complementary and alternative therapies (CATs) to lose weight. This study intends to 1) assess the utilization and perception toward CATs among obese and overweight participants and 2) assess applicability, practicality, reliability and validity of the UPCATs-Malay. Materials and methods: It was conducted cross-sectionally on 30 students and staff. Responses were analyzed using SPSS (v21). Results: Among the participants (age = 26.17±8.23 years; female = 66.7%; students = 63.3%), 40.0% were overweight and 60.0% were obese. Overall, 23.3% of the participants had previously used some types of CATs to lose weight, with herbal or dietary supplements (20.0%) being the most common. Participants’ attitudes towards CATs were mostly influenced by the internet (93.3%). Most believed that CATs modalities were safe (53.3%) and not a threat to public health (70.0%). The majority of participants (53.3%) were also considering joining any CATs-based weight management programmes. Additionally, the questionnaire was considered clear, comprehensive and not difficult to complete (< 5 minutes). The overall reliability was 0.711 (domain range = 0.641-0.881). Majority of individual items in UPCATs-Malay correlated better with their domains compared to other domains supporting validity. Conclusion: Overall, positive perceptions towards CATs were apparent and the questionnaire was reliable and valid. Further approaches should be taken especially on the identification of safe, viable CATs modalities and their role in weight management.